Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah dan Faktor Yang Menjadi Kendala Dalam Pengelolaan Keuangan Daerah Kota Tangerang Selatan - Hauralya Salsabilla; Lyndia Aziza Shafarosa; Maulika Rahmatulaili; Shahla Eliza Nurhidayah; Ivan Darmawan (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
As stated in Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council, the supervisory function is the authority given and implemented by the DPRD to the regional government in order to supervise the implementation of regional government to ensure that The policies taken are for the welfare and interests of the people. The South Tangerang City Government (Tangsel) is a new autonomous region that was born based on Law no. 51 of 2008 concerning the Establishment of South Tangerang City in Banten Province. During the first three years after its formation, the City of South Tangerang was able to extract local revenue (PAD) which came from legal taxes, levies and other things. In South Tangerang City, regional financial management is regulated by PERDA No. 2/2022 which emphasizes principles such as transparency, efficiency and accountability in the preparation of the APBD. The South Tangerang City DPRD plays a crucial role in supervising, ensuring transparency and accountability in regional financial management.